Seeking sanctuary : stories of sexuality, faith and migration / written and compiled by John Marnell. - Marnell, John (Wits University Press, 2021)
Seeking Sanctuary brings together life stories from LGBT migrants, refugees and asylum seekers living in Johannesburg and their battle to reconcile faith with their sexual and gender identity.